Adrenal gland ultrastructural changes in mice inoculated with scorpion Tityus discrepans (Buthidae) venom - Rodríguez Acosta, Alexis; Strauss, Miriam; Pulido Méndez, Magdalena; Finol, Héctor José (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
Clinical signs that appear in mice as a consequence of the toxic action by Tityus discrepans venom, such as hypotension, sweating, coldness, tachycardia, pulmonary acute oedema are accompanied by or dependant upon changes in the ultrastructural organisation of adrenal glands cellular and subcellular components. These changes may resemble the damage found in envenomed humans. To evaluate adrenal gland subcellular response to Tityus discrepans venom, ten male C57/Bl adult mice were at random divided into two groups: the experimental group was intraperitoneally injected with scorpion venom at a lethal dose of 0.5 mg/Kg of body weight and controls received saline solution by the same route. Samples from adrenal glands were taken and prepared for electronic transmission microscopic study. The samples were observed in a Hitachi- 300 electron transmission microscopy. The most relevant adrenal ultrastructural findings in this model were a great number of cortex cells that showed mitochondria and smooth endoplasmic reticulum generalised swelling. Autophagic vacuoles containing mitochondrial residues were also seen. Extensive microvasculature changes were also observed. Capillary wall changes were frequently characterised by endothelial cell cytoplasm thickening with degenerated swollen mitochondria. In some illustrations medullar capillaries wall disruption and necrosis were observed.It is suggested that adrenal gland ultrastructural damages are produced by toxins present in this scorpion venom and are responsible for some of the clinical signs observed in envenomed animals.